Genetic diversity and association analysis of the growth hormone gene in local Indonesian chicken (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The aim of this study was to investigate the effects of the Growth hormone gene, including its additive and dominant components, on laying performance (age at first laying, body weight at first laying, weight of the first egg, total eggs produced by 24 weeks, and total eggs produced by 48 weeks) and carcass attributes (live weight, carcass weight, breast weight, back weight, thigh weight, and wing weight). Materials and Methods: A total of 35 Kampung hens and 19 Sentul roosters were used in this study. Genotyping at the GH|MspI and GH|SacI loci was conducted using the restriction fragment length polymorphism (RFLP) method. Association analyses were conducted using analysis of variance, while additive and dominance effects were assessed through generalized linear models implemented in R version 4.3.1. Results: RFLP analysis revealed polymorphism at the GH|MspI locus but not at GH|SacI. No significant differences in any trait were observed among the GH|MspI genotypes. Similarly, no significant additive or dominance effects were detected. Moreover, nanopore sequencing identified two novel single-nucleotide polymorphisms, g.3242delG and g.3396_3401del, in both Kampung and Sentul chickens. Conclusion: No significant association was found between these polymorphisms and laying or carcass traits. Additionally, no significant additive or dominance effects were found, implying that these loci did not significantly influence the definition of these traits in Kampung and Sentul chickens.J. Adv. Vet. Anim. Res., 12(4): 1151–1158, December 2025http://doi.org/10.5455/javar.2025.l976